Oral microbes of pet sugar gliders and detection of Salmonella in their faeces - Hassan, Nur Diana; Abdul Aziz, Saleha; Che' Amat, Azlan; Bejo, Siti Khairani; Zakaria, Zunita; N., Fauziah (Veterinary Association Malaysia, 2016)
Clinically healthy pets may carry zoonotic pathogens and shed them, thus act as potential public health threat. Small, exotic animals are gaining popularity as pets which include iguanas, turtles and sugar gliders. Salmonellosis is an important disease affecting human and animal populations worldwide. It is reported that sugar gliders are becoming popular pets among young Malaysians, not only are they cute and adorable but are easily carried around. Of 35 pet sugar gliders and 17 from a breeder, 15% were positive for salmonellae and the serovars identified were Salmonella enterica serovar Albany (62.5%) and Salmonella enterica serovar London (37.5%). Staphylococcus spp. (41.0%) were most frequently identified from oral mucosae, followed by Enterococcus faecalis (17%), Streptococcus viridians (15.0%), Acinetobacter calcoaceticus (13.0%) and Enterococcus faecium, Pasteurella spp., Staphylococcus delphini and Escherichia coli (2.0–4.0%). The close interaction between infected pet sugar gliders and their owners poses public health risk. Breeders with infected animals present direct risk to pet shops and pet owners.